Pedagogical design of the teacher’s activity in professional educational organizations under modern conditions - Kutsba M. L., Kalugina N. A. (Interactive science, 2016)
the article is devoted to the topical problem of the design competence of teachers and masters of industrial training. Special attention is paid to the pedagogical design, analysis of components. Provisions, submitted by the authors, provide a theoretical and methodological basis of pedagogical designing of the educational environment in institutions of professional education.
Keywords: проектная деятельность; профессиональное образование; педагогическое проектирование; теоретическое обучение; Vocational education; project activity; практическое обучение; pedagogical design; theoretical and practical training